Framed - Korman Gordon 1963-; Gordon Korman (New York : Scholastic, 2011)
Griffin Bing is in big trouble when a Super Bowl ring disappears from his middle school's display case, replaced by Griffin's retainer, and the more he and his friends investigate, the worse his situation becomes.
M
730